Extraction of Alumina from Red Mud for Synthesis of Mesoporous Alumina by Adding CTABr as Mesoporous Directing Agent - Eka Putra Ramdhani; Tri Wahyuni; Yatim Lailun Ni’mah; Suprapto Suprapto; Didik Prasetyoko (Universitas Gadjah Mada, 2018)
Mines in Bintan were producing bauxite for many years. The production process of bauxite to alumina produced much red mud. From X-ray Fluorescence (XRF), alumina content on Bintan’s red mud was 28.87 wt.%. This research was studying on the extraction alumina from red mud with reduction of hematite (Fe2O3) and desilication processes. After extraction process alumina was collected about 52.89 wt.%. Synthesis of mesoporous alumina from red mud using sol-gel method at the room temperature for 72 h with cetyltrimethylammonium bromide (CTABr) as mesoporous directing agent. The CTABr/Al-salt ratio, i.e. 1.57; 4.71 and 7.85 with the sample code of AMC-1, AMC-3, AMC-5, respectively. The product was calcined at 550 °C for 6 h. The synthesized materials were characterized by X-ray Diffraction (XRD), scanning electron microscopy-energy dispersive X-ray (SEM-EDX), transmission electron microscopy (TEM), and N2 adsorption-desorption techniques. XRD pattern of AMC-1, AMC-3, and AMC-5 showed that all synthesized materials have amorphous phase. The morphology were wormhole aggregate that were showed by SEM and TEM characterization. N2 adsorption-desorption characterization showed the distribution of pore size of about 3.2 nm. The highest surface area and pore volume were obtained in solid-solid ratio CTABr/GM-AL by 1.57 (AMC-1) i.e. 241 m2/g and 0.107 cm3/g, respectively.